2023
DOI: 10.3390/ani13020250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Supplementation of Spice Extracts on Growth Performance, Nutrient Digestibility and Antioxidant Response in Broiler Chickens

Abstract: This study aimed to investigate the effects of supplementing broiler chicken diets with an encapsulated product based on capsicum and other spice (black pepper and ginger) extracts on growth performance, nutrient digestibility, digestive enzyme activity and antioxidant response. To this end, 480 1-day-old male chicks were randomly assigned to two experimental treatments (12 pens/treatment; 20 birds/pen). Dietary treatments included a basal diet with no additives (CONTROL) and a basal diet supplemented with 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Present results revealed that the combination of capsicum, black pepper, and ginger oleoresins, and cinnamaldehyde promoted somatic growth in gilthead seabream (BW f and SGR) at both dietary levels tested (0.1% and 0.15%). Such results are partially in accordance with those obtained when testing the same combination of pungent spices in broiler chickens, with production phase differences that can be attributed to inherent differences in species-specific physiology, production system, diet formulation, among other factors ( 41 ). In fish species, there is still scarce information on the pungent spices herein tested.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Present results revealed that the combination of capsicum, black pepper, and ginger oleoresins, and cinnamaldehyde promoted somatic growth in gilthead seabream (BW f and SGR) at both dietary levels tested (0.1% and 0.15%). Such results are partially in accordance with those obtained when testing the same combination of pungent spices in broiler chickens, with production phase differences that can be attributed to inherent differences in species-specific physiology, production system, diet formulation, among other factors ( 41 ). In fish species, there is still scarce information on the pungent spices herein tested.…”
Section: Discussionsupporting
confidence: 85%
“…Bile acid (BA) quantification was performed as previously described by Herrero-Encinas et al. ( 41 ) with modifications. BA extraction from gallbladder bile samples was performed by extraction of 100 µL of water-diluted bile (1/2,000) with 400 µL of acetonitrile (ACN) containing internal standard (chenodeoxycholic acid-d4, CDCA-d4).…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient apparent digestibility reflects the absorption of nutrients in animals, while nitrogen metabolism indicates their efficiency in utilizing proteins. Previous studies have demonstrated that plant extracts can enhance the digestion, absorption, and utilization of dietary nutrients [27,28]. However, some studies have found no improvement in nutrient utilization despite supplementing diets with plant extracts [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Varmaghany et al [45] reported that the addition of 15 g of olive leaves per kg of feed reduced the feed intake in broilers. Supplementation of the diets with phytogenics might increase nutrient digestibility by increasing digestive enzyme secretion and improving epithelial integrity, bile acid secretion, GIT motility and the microbiota profile of the cecum [46][47][48][49][50][51]. Moreover, the maturation of the intestinal mucosa as well as the growth of the main components of the GIT occur during the first 10 d of age [52], and consequently, the positive effects of the polyphenols may be more noticeable in young birds.…”
Section: Growth Performancementioning
confidence: 99%